Facing the climate emergency : how to transform yourself with climate truth - Salamon, Margaret Klein, 1986-; Gage, Molly, 1978- (New Society Publishers, 2020)
"Facing the Climate Emergency addresses the fears of everyone who is alarmed about the climate crisis and yet feels powerless to stop it. Drawing on psychology, it shows readers how to use their feelings of fear, grief, and powerlessness to transform themselves into climate warriors and motivate collective change."--